A Feasible Industrialized Process for Producing High Purity Diacylglycerols with No Contaminants. Issue 10 (22nd August 2019) - Li, Daoming; Qin, Xiaoli; Sun, Baoguo; Wang, Weifei; Wang, Yonghua
Abstract : Industrial production of high purity diacylglycerols (DAGs) is still a challenge around the world because of contaminant formation during DAG production, such as glycidyl esters (GEs), 3‐chloro‐1, 2‐propanediol esters (3‐MCPDEs), and trans fatty acids (TFAs). This study develops a feasible industrialized process for producing high purity DAGs with no contaminants by combining enzymatic esterification, three‐stage molecular distillation, bleaching, and stream stripping deodorization. After immobilized SMG1‐F278N‐catalyzed esterification in a packed bed reactor at 30 °C, the product contains 50.87% DAGs, 32.82% monoacylglycerols (MAGs), and 16.31% FAs. The resultant DAGs are subsequently purified by a three‐stage molecular distillation at 150, 160, and 160 °C, respectively, followed by bleaching under vacuum (2 kPa) at 65 °C and deodorization under vacuum (100 Pa) at 160 °C. Contaminants containing GEs, 3‐MCPDEs, and TFAs are undetectable throughout the whole process of DAG preparation. The final DAG product contains 99.74% DAGs and shows good quality indices (peroxide value of 2.05 mmol kg −1 and undetectable acid value). Overall, this study proposes a new industrial strategy for the production of DAGs with high purity and quality, which may promote the re‐commercialization of DAGs in the near future. Practical Applications : DAGs were widely sold in Japan and America as healthy cooking oils owing to their health promoting properties, however, sales of DAGs were stopped after the detection of the potential carcinogen of GEs seriously exceeded the allowed value in DAGs. This study proposes a feasible industrialized process for producing high purity and quality DAGs with no contaminants including GEs, 3‐MCPDEs, and TFAs. The immobilized SMG1‐F278N that fills in packed bed reactor for DAG production can be used for at least a half year without significant loss in its esterification activity, indicating that the proposed process is an economical process. Overall, the proposed economical strategy may shed light for future production of edible, available, and safe DAGs. A feasible industrialized process for producing high purity diacylglycerols (DAGs) with no contaminants is proposed. Overall, the proposed economical strategy may shed light for future production of edible, available, and safe DAGs. Abstract : A feasible industrialized process for producing high purity diacylglycerols (DAGs) with no contaminants is proposed. Overall, the proposed economical strategy may shed light for future production of edible, available, and safe DAGs.